Students’ Ability In Pronouncing Vowels Based On “Sound Of English” - Erlian Dwisnu (Jurnal Multidisiplin Dehasen (MUDE), 2023)
This research is intended to know and describe Students Ability in Pronouncing Vowels Based on “ Sound of English. The problem was How is the Ability of students’ in pronouncing vowels based on “Sound of English”?. This research is just focused on the students’ ability in pronouncing vowel sounds consists of [i:], [ I], [ʊ], [u:], [ e], [ ә], [З:], [ᴐ:], [æ], [ʌ], [ɑ:], and [ɒ]. In this research the researcher used descriptive method. There were 65 students that the researcher folowed this research. pronounciaton test was used to collect the data in this research, it consisted of 48 items in pronounciation test. The data was evaluated and analyzed by “Sound of English”. The result of this research showed the students’ ability in pronouncing vowel was good almost in all of vowel sounds like [e] was 99.23%. The sound [æ] was 97.69%. The sound [ɑ:] was 96.38%. Then sound [З:] was 94.23%, sound [ʊ] was 93.46% and [I] was 90.76% . After that [ә] was 87.30%. The sound [u:] was 84.61%. Then, [i:] was 79.61% and The sound [ᴐ:] was 78.46%. After that [ɒ] was 61.15% and the last sound [ʌ] was 60.38%. Almost all the participant in this reserach was succes to pronounce vowel sounds. It means that phonology lecturers have succeeded in teaching. The researcher suggested, the lecturers give more exercises to the students in order that they can practice their pronunciation not only for the purpose of studying phonology but also in the application of their daily activities.